(untitled) (Annals of Medical Research, 2021)
Aim: Crohn’s disease and ulcerative colitis are included in inflammatory bowel disease (IBD). The study aimed to compare the healing effects of two promising therapeutic agents: Platelet Rich-Plasma and Thymoquinone (TQ) on DSS induced IBD. Materials and Methods: The animals were divided into three groups as IBD (n=10), PRP treatment (n=10) and TQ treatment (n=10). Experimental IBD was initiated through the oral intake of 5% Dextran Sodium Sulfate (DSS) in drinking water. PRP (0.5 cc) and thymoquinone dissolved in distilled water (100mg/kg) were daily administered rectally to PRP treated group animals for seven days. All animals were sacrificed and rectal tissue calprotectin, lactoferrin and hydroxyproline levels were assessed on the seventh day. Total antioxidant status (TAS), total oxidant status (TOS) and oxidative stress index (OSI) levels were statistically compared. Results: Rectal tissue calprotectin, lactoferrin and hydroxyproline levels were higher in the IBD group (p<0.001, p<0.001 and p<0.001, respectively). TQ treated group animals had lower rectal tissue lactoferrin levels (p<0.011) and TOS and OSI levels (p=0.001 and p=0.001, respectively) than PRP group animals and also the highest antioxidant capacity. Conclusion: Calprotectin, lactoferrin, and hydroxyproline levels are valuable markers in the presence of IBD and response to treatment. Oxidative stress is an important problem that cannot be avoided in unattended cases. Our experimental IBD model found TQ treatment to be more effective in healing than PRP treatment.